The deep search of knowledge: George Chapman’s glosses in The Shadow of Night (1594) - Silvares, Lavinia (Acta Scientiarum. Language and Culture, 2017)
This paper addresses the glosses of the first edition of George Chapman’s philosophical elegy, The Shadow of Night (1594), as a specific and common practice of prescriptive work, produced by Renaissance authors following the ancient tradition of the auctoris interpretatio. Assuming the gloss as an exposition and scrutiny of the places of poetic invention and elocution, Chapman puts himself in the position of both annotator and authorizer of his text, defining a particular legibility for the poem within the learned circles of the English court of Shakespeare’s time. Considering the view of the glossarial practice as an emulation of the ancient scholium work of ‘exposing the difficulties’ of a literary text and thus legitimizing it as fit to enter the proper tradition, this paper discusses, 1. the implications of Chapman’s glosses for the poem’s immediate reception; 2. the importance of authorized role models (Servius, Macrobius, Cornutus) for the glossarial practice; and 3. the idea that a text does not possess a congenital clearness of its own, but can only be understood through the continuous process of a specific glossarial assessment.